Juridical Analysis of Cash Rejection in Consumer Transactions on Cashless Payment Practices in Indonesia - Alamanda, Asri Elies; Mangar, Irma; Yasin, Bukhari; Pangestika, Pingkan Widya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2026)
The development of digital payment systems in Indonesia encourages the increasing use of non-cash transactions in goods and services trading activities. However, in the midst of this transformation, the practice of refusing cash payments by business actors has emerged for reasons of efficiency, security, and internal company policies. This practice raises juridical problems because Rupiah money as a legal tender in Indonesian territory must be accepted in every transaction as stipulated in Law Number 7 of 2011 concerning Currency. The research method used is normative legal research. The results of the study show that the practice of refusing cash payments is basically contrary to the legal provisions regarding the obligation to use Rupiah and has the potential to violate consumers' rights to obtain fair and non-discriminatory services. On the other hand, the development of digital payment systems is also supported by government policies in realizing economic efficiency and financial inclusion. Therefore, there is a need for harmonization of regulations that provide legal certainty between the obligation to receive cash and the payment digitalization policy, so that the protection of consumer rights remains guaranteed without hindering the innovation of the national payment system.